2014
DOI: 10.18632/aging.100686
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic clock generates nutrient anticipation rhythms in mTOR signaling

Abstract: The mTOR signaling pathway modulates metabolic processes with respect to nutrient availability and other growth-related cues. According to the existing paradigm, mTOR complex 1 (mTORC1) activity in vivo is induced by food and gradually decreases during fasting. We found that mTORC1 activity is controlled by an internal clock mechanism different from the known light-entrainable circadian clock. We observed 24-hr rhythms in phosphorylation of mTORC1 downstream targets, which were entrained by food, persisted dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 15 publications
2
45
1
Order By: Relevance
“…Moreover, some of the pathways represented among the genes oscillating only in the Arntl KO mice were linked to translation and ribosome biogenesis (Supplemental Table S2). The rhythmic activation of TORC1 in Arntl KO mouse liver may seem contradictory to previous results, which have shown liver TORC1 activation to be under circadian clock control; rhythmicity was maintained under constant darkness and under conditions of starvation (Jouffe et al 2013), and translation and ribosome biogenesis was dependent on the circadian clock in various organisms (Dong et al 2008;Piques et al 2009;Xu et al 2011;Jouffe et al 2013;Khapre et al 2014). More recent results, however, have pointed to a pivotal role of feeding rhythms in rhythmic translation of TOP mRNAs (Atger et al 2015).…”
Section: Org Downloaded Fromcontrasting
confidence: 69%
“…Moreover, some of the pathways represented among the genes oscillating only in the Arntl KO mice were linked to translation and ribosome biogenesis (Supplemental Table S2). The rhythmic activation of TORC1 in Arntl KO mouse liver may seem contradictory to previous results, which have shown liver TORC1 activation to be under circadian clock control; rhythmicity was maintained under constant darkness and under conditions of starvation (Jouffe et al 2013), and translation and ribosome biogenesis was dependent on the circadian clock in various organisms (Dong et al 2008;Piques et al 2009;Xu et al 2011;Jouffe et al 2013;Khapre et al 2014). More recent results, however, have pointed to a pivotal role of feeding rhythms in rhythmic translation of TOP mRNAs (Atger et al 2015).…”
Section: Org Downloaded Fromcontrasting
confidence: 69%
“…Indeed, it has been shown that the TORC1 pathway is rhythmically activated in mouse liver (12,49), hippocampus (50), and SCN (51), influencing in this way rhythmic ribosome biogenesis (12) or light response and circadian behavior (52,53). Moreover, the circadian clock, in coordination with feeding rhythms, seems to play a modulating role in this activation (12,54,55). Although we confirmed the rhythmic activation of the TORC1 pathway in mouse liver, it seemed that Bmal1 deletion had no effect on the rhythms of TOP genes translation; in particular, the amplitudes were indistinguishable (Fig.…”
Section: Translation Efficiency Is Regulated During the Diurnal Cyclementioning
confidence: 99%
“…Activity of the mTOR pathway in the suprachiasmatic nucleus (SCN) is stimulated by light and mutations in the mTOR kinase itself or in the mTOR effector protein eukaryotic initiation factor 4E binding protein (4E-BP) regulate circadian timing(Cao et al, 2011; Cao et al, 2015; Cao et al, 2008; Cao et al, 2010; Cao et al, 2013). Interestingly, mTOR pathway activity demonstrates circadian oscillations(Cao et al, 2013; Cornu et al, 2014; Jouffe et al, 2013; Khapre et al, 2014; Lipton et al, 2015). Heterozygous mutations of either mTOR in mice or Tsc1/2 orthologs in Drosophila clock neurons can result in circadian arrhythmia, together suggesting that a delicate balance of mTOR signaling is required for optimizing circadian synchrony(Cao et al, 2013; Zheng and Sehgal, 2010).…”
Section: Introductionmentioning
confidence: 99%